Marketing Strategy for Facing Changes in Consumer Behavior in Disruption Era - Wijaya, I Gusti Ngurah Satria; Wulandari, Riza; Malintang Latanro, Annisa Balqis Bashira Syahrir; Sugianitri, Ni Nyoman Arie Rahayu (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : This study aims to analyze marketing strategies in dealing with changes in consumer behavior of generation Y and generation Z in the era of disruptionDesign/Methode/Approach : The analysis technique of this research is interactive analysisResearch Finding : The outcomes of research are conventional marketing strategies are still proven to be effective in accompanying digital marketing strategies in this era of disruption, in other words, the digital marketing strategy formed in this study is a development of the marketing mix strategy, especially the online promotion part as a result of changes in the behavior of the two generations in this era of disruptionTheoretical contribution/Originality : Provides reinforcement of the theory of marketing strategies used in dealing with changes in the behavior of generations Y and Z in this era of disruptionPractitionel/Policy implication : Provide policy recommendations for company management for marketing strategies used in dealing with changes in the behavior of generations Y and Z in this era of disruptionResearch limitation : The limitation of this research is still a qualitative method so that in the future it will be strengthened by using a quantitative method